(untitled) - Hirschmeier, Johannes (Cambridge, 1968)
This book is concerned with the beginning phases of Japan's industrialization until about 1895. A group of dynamic entrepreneurs had a particularly important role in this process.
Keywords: Businessmen,Industries,Doanh nhân,Công nghiệp; Japan,Japan,Nhật Bản,Nhật Bản